Electrogastrography in experimental pigs: the influence of gastrointestinal injury induced by dextran sodium sulphate on porcine gastric erythromycin-stimulated myoelectric activity - Tachecí, Ilja; Kvetina, Jaroslav; Kunes, Martin; Edakkanambeth Varayil, Jithinraj; Ali, Shahzad Marghoob; Pavlik, Michal; Kopacova, Marcela; Rejchrt, Stanislav; Bures, Jan; Pleskot, Miloslav (Neuro endocrinology letters, 2011)
OBJECTIVES: Electrogastrography (EGG) is a non-invasive investigation of gastric myoelectrical activity. The aim of study was to evaluate the impact of erythromycin on EGG in gastrointestinal toxic injury induced by dextran sodium sulphate (DSS) in experimental pigs. METHODS: The experiments were carried out on 12 adult pigs (weighing 30-35 kg). EGG was recorded using Digitrapper equipment (Synectics Medical AB, Stockholm). Running spectrum activity was used for EGG evaluation. There were two groups of animals: Group I: 6 controls with erythromycin administration (1,600 mg intragastrically); Group II: 6 animals treated with DSS (for 5 days, 0.25 g/kg per day in a dietary bolus) followed by erythromycin administration. Baseline and subsequent six separate 30-minute EGG-recordings (from time 0 to 360 min) were accomplished in each animal. RESULTS AND CONCLUSION: A total of 84 records were analysed. Baseline dominant frequency of slow waves was fully comparable in both groups. In Group I, there was a significant increase in dominant frequency after erythromycin administration (maximum between 240-360 min). There was a flat non-significant and delayed increase in dominant frequency after erythromycin administration in Group II. The difference between Group I and II at particular time intervals was not significant but a diverse trend was evident. EGG recording enables us to register a gastric myoelectrical effect of prokinetic drugs. Erythromycin induced a significant increase in the dominant frequency of slow waves. DSS caused toxic injury to the porcine gastrointestinal tract responsible for the delayed and weaker myoelectrical effect of erythromycin in experimental animals.
Keywords: erythromycin; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; Sus scrofa; Electrophysiological Phenomena; Stomach; Dextran Sulfate; Female; Gastrointestinal Agents; modely u zvířat; gastrointestinální nemoci; zvířata; elektrofyziologické jevy; Electromyography; síran dextranu; ženské pohlaví; žaludek; Models, Animal; gastrointestinální látky; Animals; Gastrointestinal Tract; Gastrointestinal Diseases; elektromyografie; gastrointestinální trakt; Erythromycin